Human Capital and Perceived Usefulness on Perceived Profitability: Study of Accounting Information Acquisition in SMEs - Nurim, Yavida; Putri, Agatha Fitria; Harjanto, Nung; Elrifi, Muhammad Yudhika (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The study examines the role of perceived usefulness of accounting information system as a mediation on human capital and perceived profitability relationship in information system acquisition. Prior research proved that the quality of accounting information system has positive correlation with the quality of accounting practice through effective and productive reporting. According to SMEs, human capital is one of important factors in accounting information because in fact SMEs is labour intensive and owned by families. However, empirical evidence showed that there is inconsistent relationship between human capital and perceived profitability on accounting information investment. In other side, SMEs face source limitation in accounting information investment. Therefore, this study uses a mediation perceived usefulness of accounting information system for examination relationship. The examination uses survey data from SMEs in Special Region of Yogyakarta (DIY) because the SMEs do not yet adequate financial governance in daily operation. Based on survey of 124 respondents, this study revealed that the accounting system capability in producing the quality information of daily activities encourage SMEs implement accounting information acquisition. SMEs consider the important of accounting information in increasing profitability. This evidence contributes to stakeholder, especially government, in provide an assistant for SMEs’ financial governance.